DESIGNING CAMTASIA SOFTWARE ASSISTED LEARNING MEDIA TOWARD STUDENTS’ MATHEMATICAL COMPREHENSION IN NUMERAL MATERIAL - Setiyani Setiyani; Dian Permana Putri; Derin Prakarsa (IKIP Siliwangi and I-MES, 2019)
This study aims to determine the feasibility of learning media in the form of videos with the help of camtasia software on number material using the R & D (Research and Development) methodology with ADDIE models (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at Cirebon State MTs 2 Cirebon in class VII. The research instrument used was an interview questionnaire for teachers and students, a practicality questionnaire for students and a validation sheet for three lecturers as well as a mathematics teacher. From the results of the instruments in the form of interview questionnaires students are clear that students prefer learning with the presence of learning media and the results of teacher interviews that result in a lack of facilities for the learning process using learning media. The instrument results in the form of a validation questionnaire produce an average score of 85% (very valid), so that it can be said that the learning media in the form of videos are valid and can be used. The instrument of practicality questionnaire filled by nine students with three high-ability students, three moderate-capable students, three low-ability students produced an average score of 86.77%, it can be said that the practice was very high. Based on the results of each instrument, it can be stated that the learning media in the form of CD-shaped videos is practical and can be used.